Improving Students' Learning Motivation Through Differentiation Learning Based on Cooperative Learning - Akhnah, Al Manunal; Ririn Masrikah; Nugroho Kartijono (Bioeduca : Journal of Biology Education, 2024)
In the 21st century, education focuses on maximizing students' potential to face current global challenges. Therefore, appropriate learning strategies, including differentiated instruction, are needed to meet these demands. This study aims to determine the increase in students' motivation to learn biology after implementing differentiated instruction. This study is a classroom action research. The subjects of this research are 36 eleventh-grade students. The object of this research is the student's motivation to learn biology after participating in differentiated instruction based on Cooperative Learning. The questionnaire is the data collection method used to gather information on students' motivation to learn biology. The data analysis technique used in this classroom action research is descriptive quantitative analysis. The study's results proved an increase in learning motivation, as indicated by the questionnaire analysis results showing 82.14% in the first cycle and 86.57% in the second. Thus, these results indicate that the implementation of differentiated instruction based on Cooperative Learning can increase the learning motivation of eleventh-grade students at SMA N 4 Semarang in the coordination system material